An examination of South Africa’s efforts at patent system reform: trips flexibilities fully appropriated for public health needs? - Lakpini, Clarence Sokolambe (Department of Commercial Law, 2020)
The question that underlies this research is whether and to what extent does South Africa’s moves to amend its Patent Act, as outlined in the country’s new Intellectual Property (IP) Policy take advantage of the flexibilities made available through the Agreement on Trade- Related Aspects of Intellectual Property (TRIPS)? Patents law and access to medicines are two areas which are not new to South African IP law. Since the late 1990s when the Human Immunodeficiency Virus (HIV) was at its peak, there has been a tensed relationship between IP, through patents, and access to medicines. While proponents for pharmaceutical patents have argued that patents are a necessary stimulant for innovation and development of new medicines, those against pharmaceutical patents have vigorously laid blame on the patent system for birthing monopolies which have led to unaffordable prices for many life-saving drugs. This dissertation examines the patent framework of South Africa and juxtaposes it with the TRIPS Agreement to determine if there is a gap with the regards to the flexibilities available under each, and if so, how much of a gap exists between them. Also, the recommendations made in the IP Policy which was released by the Department of Trade and Industry (DTI) in 2018, are evaluated to ascertain how aligned to the TRIPS flexibilities they will be if they are turned into law by the lawmaker. The Indian patent system is also looked at to see how it went about patent reform and what South Africa can learn from it. Finally, conclusions are drawn and recommendations made, regarding model language which reflects the recommendations in the Policy that the lawmaker may refer to in the amendment process. Patent reform is a difficult task, and with lives hanging in the balance, a crucial one. The process in South Africa has lingered for many years without resolution. This dissertation highlights the need for urgency in the process with the hope that these changes catalyse into a more equitable patent system where the IP scale provides a more balanced eco-system in which both pharmaceutical patent owners and the general public who rely on their medicines can thrive. Although, a daunting task, a bold and proactive approach must be taken to ensure that the balance is reached timeously and efficiently.